Health psychology - Rodham, Karen, 1970- (New York : Palgrave MacMillan, 2010)
'This introduction to health psychology is an invaluable resource for students looking to go beyond the basics in their studies. It includes sections on the influences of health behaviour and approaches to health promotion, as well as providing an overview of key health issues such as stress and eating disorders'--Provided by publisher.
Machine generated contents note: Introduction &--Overview -- What is Health Psychology? -- SECTION ONE: HEALTH BEHAVIOUR -- What is Health Behaviour? -- Influences on Health Behaviour? -- Explaining Health Behaviour: Cognitive Models -- SECTION TWO: HEALTH PROMOTION -- What is Health Promotion? -- How is Health Promotion evaluated? -- SECTION THREE: EXAMPLES_OF HEALTH ISSUES IN_PSYCHOLOGY -- Stress -- Coping with Stress -- Eating Behaviour -- Treating/Managing Anorexia, Bulimia, Obesity.
Includes bibliographical references (p. 173-205) and index.
Keywords: Clinical health psychology; Health behavior; Health promotion; Mental health